Racial and Ethnic Differences in Limiting Life-Sustaining Treatment in Trauma Patients. (November 2019) - Hanna, Kamil; Palmer, James; Castanon, Lourdes; Zeeshan, Muhammad; Hamidi, Mohammad; Kulvatunyou, Narong; Gries, Lynn; Joseph, Bellal
Introduction: Differences in health care between racial and ethnic groups exist. The literature suggests that African Americans and Hispanics prefer more aggressive treatment at the end of life. The aim of this study is to assess racial and ethnic differences in limiting life-sustaining treatment (LLST) after trauma. Study Design: We performed a 2-year (2013-2014) retrospective analysis of Trauma Quality Improvement Program database. Patients with age ≥16 and Injury Severity Score (ISS) ≥ 16 were included. Outcome measures were the incidence and the predictors of LLST. Multivariable logistic regression was performed to control for confounding variables. Results: A total of 97 024 patients were identified. Mean age was 49 (21) years, 68% were male, 68% were white, and 14% were Hispanic. The overall incidence of LLST was 7.2%. Based on race, LLST was selected as consistent with goals of care more often in white when compared to African American individuals who experience serious traumatic injury (8.0% vs 4.5%; P < .001). Based on ethnicity, LLST was more often selected in non-Hispanics (7.5% vs 5.2%, P < .001) when compared to Hispanics. On regression analysis, the independent predictors of LLST were white race (odds ratio [OR]: 2.7 [1.6–4.4], P = .02), non-Hispanic ethnicity (OR: 1.9 [1.4-4.6]; P = .03), severe head injury (OR: 1.7 [1.1-3.2]; P = .04), and ISS (OR: 3.1 [2.4-5.1]; P < .01). Conclusions: Differences exist in selecting LLST between different racial and ethnic groups in severe trauma. African Americans and Hispanics are less likely to select LLST when compared to whites and non-Hispanics. Further studies are required to analyze the factors associated with selecting LLST in African Americans and Hispanics.